Dual Nationality of the Ships and its Legal Impact - Aladwan, Zaid (Faculty of Law, Hasanuddin University, 2020)
The international conventions for high seas had provided that each ship must have one flag only and must not change its flag during the voyage or for any reason. However, in the last years many ships have infringed this rule and had registered with other states that had allowed any foreign ships to register in their ports. These states are an open registry states, which are known as 'Flag of Convenience' states.Â This change of the flag during the voyage, which caused a lot of problems, was for a political and economic reasons either to make their own profit or to avoid their flag state fees. Notably, such phenomenon is considered as a maritime fraud, which will impact the maritime world and disseminate chaos on the high seas.Â For these reasons, this paper will highlight the duplication of the nationality for the ships issue and analyse the effects of this negative behaviour.Â